Peran Direksi Wanita dalam Memoderasi Performa Perusahaan Terhadap Pengungkapan Sukarela Integrated Reporting - Ivone, Ivone; T.G, Natasya Des (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
Integrated reporting is a new development in the world of reporting that combines company financial and non-financial information. This study aims to prove the effect of company performance on integrated reporting disclosures with female directors as a moderating variable. The research object is a non-financial company registered with the Value Reporting Foundation for the period 2017 – 2021. The research was conducted through logistic regression tests and moderated regression analysis (MRA) tests. The results of the study show that ROA has a significant positive effect on integrated reporting disclosures. Meanwhile, ROE and MBVE have a significant positive effect on integrated reporting disclosure with moderation of female directors. Female directors are able to moderate the relationship between company performance and voluntary disclosure of integrated reporting. Keywords: Firm Performance, Gender Diversity, Integrated Reporting, Voluntary Disclosure